Electrochemical behavior of steel bars in magnesium phosphate cement. (July 2023) - Tang, Hao; Qian, Jueshi; Qin, Jihui; Li, Zhen; Jia, Xingwen; Yue, Yanfei; Dai, Fumin
Abstract: The electrochemical characteristics of steel bars in magnesium phosphate cement (MPC) are crucial when applying MPC to reinforced concrete. In this study, the electrochemical behaviors of steel bars in MPC were investigated via electrochemical tests combined with surface analyses. The results indicated that the steel bars in the simulated MPC pore solution could effectively passivate, forming films that mainly consisted of FePO4 . In the MPC matrices, the continuous precipitation of phosphates led to the accumulation of passive films, which were responsible for the superior corrosion protection of MPC compared to traditional cement materials. MPC exhibited a self-healing corrosion feature after the depassivation of steel bars, which could be characterized by the dramatic recovery of passive film resistance and charge transfer resistance. Furthermore, the corroded steel bars in MPC with a low magnesia-to-phosphate ratio could re-passivate and stabilize for long periods of time.